1995
DOI: 10.1128/jvi.69.5.3206-3210.1995
|View full text |Cite
|
Sign up to set email alerts
|

Engineered serine protease inhibitor prevents furin-catalyzed activation of the fusion glycoprotein and production of infectious measles virus

Abstract: We have identified the major cellular endoprotease that activates the fusion (F) glycoprotein of measles virus (MV) and have engineered a serine protease inhibitor (serpin) to target the endoprotease and inhibit the production of infectious MV. The F-protein precursor of MV was not cleaved efficiently into the mature F protein in human colon carcinoma cells lacking functional furin, indicating that furin is the major enzyme responsible for activation of the MV F protein. A human serpin ␣ 1-antitrypsin variant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 27 publications
0
51
0
1
Order By: Relevance
“…Furin-adapted a 1 -ATs have been shown to efficiently inhibit the formation of infectious progeny of other viruses (e.g. HIV, measles virus and human cytomegalovirus) [38,39,40,41,68,69]. Using a replication-competent recombinant VSV pseudotyped with the LASV glycoprotein GP [48], we demonstrate that proteolytic maturation of the precursor GP-C is sensitive to S1Padapted a 1 -ATs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furin-adapted a 1 -ATs have been shown to efficiently inhibit the formation of infectious progeny of other viruses (e.g. HIV, measles virus and human cytomegalovirus) [38,39,40,41,68,69]. Using a replication-competent recombinant VSV pseudotyped with the LASV glycoprotein GP [48], we demonstrate that proteolytic maturation of the precursor GP-C is sensitive to S1Padapted a 1 -ATs.…”
Section: Discussionmentioning
confidence: 97%
“…Due to the introduction of a second mutation from alanine to arginine at P4 of the RCL, the engineered a 1antitrypsin variant Portland (a 1 -AT-PDX) showed high affinity for furin [38]. a 1 -AT-PDX efficiently inhibited the formation of infectious HIV, measles virus, and human cytomegalovirus progeny by blocking furin-dependent processing of glycoproteins gp160, F0 and gB, respectively [38,39,40,41]. Pullikotil and coworkers used this approach for the generation of highly selective a 1 -antitrypsin variants specific for S1P by introducing various S1P recognition motifs into the RCL of a 1 -antitrypsin [42].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular note is that the crystal structure of the uncleaved form of the human H1 hemagglutinin (HA) from Influenza virus showed that the cleavage event only minimally alters the local structure of the transmembrane glycoprotein and its antigenic sites (Stevens et al, 2004). In addition, in vitro and in vivo studies on several viruses have shown that Env glycoprotein cleavage is not always necessary for virus maturation/assembly or infectivity, implying that cleavage has little effect on function (Bos, Luytjes, and Spaan, 1997;Hingley, Leparc-Goffart, and Weiss, 1998;Russell, Dalrymple, and Johnston, 1989;Watanabe et al, 1995). However, these conclusions are often derived from one-step infection assays; it is possible that additional selection pressures are exerted in multiple replication rounds, and/or in vivo, that result in the retention of the highly conserved cleavage motif.…”
Section: Discussionmentioning
confidence: 99%
“…The fusion protein of measles virus is produced by processing of a precursor (F 0 ) at a R-R-H-K-R sequence (46). Expression of correctly processed F-protein in Vero cells leads to membrane fusion and formation of syncytia.…”
Section: Viral Infectionmentioning
confidence: 99%